The Effect of Payer Type, Disposition, and Day of Surgery on Resource Consumption following Hip Fracture Care - Barinaga, Gonzalo; Sayeed, Zain; Anoushiravani, Afshin A.; Wright, Erik; El-Othmani, Mouhanad M.; Cagle, Paul J.; Saleh, Khaled J. (The Journal of Hip Surgery, 2017)
As we shift from a fee-for-service to value-based reimbursement system, it is critical that orthopaedic surgeons assess all characteristics of the patient prior to surgical intervention. The purpose of this study was to evaluate the relationship of payer type and disposition on direct and indirect measures of resource consumption (length-of-stay [LOS], hospital cost, and 30-day readmission). Patients equal to or more than 55 years of age with radiographic evidence of hip fracture necessitating surgical intervention were included. Initially, baseline characteristics, including age, body mass index (BMI), American Society of Anesthesiologist (ASA) score, fracture type, and instrumentation, were reported by payer type (private versus Medicare) and disposition (skilled nursing facility [SNF], home, and home health). In the second phase, the independent effects of payer type and disposition on resource consumption were evaluated. Lastly, the impact of payer type and day of admission on disposition were assessed. A total of 478 patients met the inclusion criteria. Evaluation of baseline characteristics demonstrated that age and ASA scores were significantly higher within the Medicare and SNF cohorts, when compared with private payers and home/home health, respectively. Medicare as a payer type resulted in an increased LOS (5.6 versus 4.5 days) and greater hospital cost (12.1%) than private payers. Moreover, payer type was not predictive of 30-day readmission. Disposition following operative fixation resulted in an average LOS of 5.8, 4.4, and 4 days for patients discharged to SNF, home, and home health, respectively. No significant difference in hospital stay was noted between home and home health patients. Compared with patients discharged home, in-hospital cost was 33.9 and 12.3% greater for the SNF and home heath cohorts, respectively. Finally, 21.6% of patients discharged to a SNF were readmitted within 30 days. Our results indicate Medicare patients and those discharged to a SNF are more likely to have longer LOS and incur greater costs. Additionally, 30-day readmission is significantly higher in patients discharged to SNF. Thus, patients with hip fracture should be rigorously optimized within the preoperative setting to enhance clinical outcomes. Moreover, additional resources should be allocated to the higher risk patients.
Keywords: hip fracture; resource utilization; discharge disposition; day of admission; payer type